How do women with a diagnosis of Borderline Personality Disorder detained in secure and locked services perceive recovery?: a grounded theory - Canacott, Louise (2019)
The principles of connectedness, hope, identity, meaning in life and empowerment (CHIME) are seen to underpin personal recovery. Studies to date have researched experiences of recovery across mental health services, including forensic services and services for individuals diagnosed with personality disorder. However, the needs of women diagnosed with Borderline Personality Disorder in secure services has not been explored. This study developed a grounded theory of the experiences of seven women. Participants described how they adjusted psychologically as they progressed through stages in their recovery. Relationships were the key facilitative factor for recovery but also a common source of setbacks.